2003
DOI: 10.1046/j.1464-410x.2003.04224.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin as an inducer of fibrosis in the tunica albuginea of the rat: a new animal model of Peyronie's disease

Abstract: RESULTSAt 1 week after injection of fibrin into the rat TA, only oedema was present; at 3 weeks, the oedema developed into a characteristic fibrotic PD-like plaque. The injection of TGFb 1 into the TA also induced oedema in the TA at 1 and 3 weeks but there was very little evidence of a recognisable plaque at either time. Injection with TGF-b 1 plus fibrin resulted in oedema at 1 week but at 3 weeks there was a smaller plaque than with fibrin only. At 6 weeks the induced plaques in the fibrin-only and fibrin +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 39 publications
0
82
0
5
Order By: Relevance
“…during sexual activity) can result in delamination of the tunica albuginea and microvascular damage (8,15). Fibrin was found to be potentially involved in the development of the fibrotic plaque in a murine model of PD (16). In the same study, and in another more recent (17), was also reported the presence of increased levels of PAI-1, an important inhibitor of fibrinolysis and collagenolysis: its increased activation appears to play a key role in the development of penile plaque.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…during sexual activity) can result in delamination of the tunica albuginea and microvascular damage (8,15). Fibrin was found to be potentially involved in the development of the fibrotic plaque in a murine model of PD (16). In the same study, and in another more recent (17), was also reported the presence of increased levels of PAI-1, an important inhibitor of fibrinolysis and collagenolysis: its increased activation appears to play a key role in the development of penile plaque.…”
Section: Discussionmentioning
confidence: 81%
“…Based on these innovative clinical and histological findings has assumed a possible application of lipofilling technique in patients with PD. It was therefore drawn up an experimental protocol consists of two basic steps: 1. creating an animal model of PD on the basis of experiments already conducted (16,25) have all been taken into account, but basically considered to be associated with erectile dysfunction more than strictly to PD. Microscopically, the tunica albuginea is largely composed by fibrillar collagen type I, woven with elastin fibers, in order to form organized structures (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better knowledge of Peyronie's disease pathogenesis could help us have more treatment options. Therapy options, particularly for the late phase of Peyronie's disease are severely limited [4,5]. No medical treatment that can relieve all symptoms in patients with Peyronie's disease is currently available.…”
Section: Discussionmentioning
confidence: 99%
“…The primary reason for this and the cause of the PD plaque is unknown and the molecular pathology is poorly understood, although it is thought that often the plaque develops as the result of an abnormal wound healing process after a TA trauma [4][5][6]. Peyronie's disease is characterized by development of a fibrotic plaque [7].…”
Section: Introductionmentioning
confidence: 99%